Analisis Determinan Tingkat Pengangguran Se Eks Karesidenan Surakarta Di Jawa Tengah Tahun 1999- 2013 - Panjawa, Jihad Lukis, Dr. Daryono Soebagyo, M.Ec (2015)
This research aimed to analyze the effect of Gross Regional Domestic Product (GDP), inflation, the minimum of wage, population and unemployment rates throughout the year 1999-2013 in Surakarta Residency. The analysis technique used in this study is a panel data regression. It used to determine the factors that affect the level of unemployment in Surakarta Residency along 1999-2013. Data panel is a combination of cross section that includes seven in Surakarta and time series during 15 years from 1999-2013. The results showed that the Fixed Effects Model (FEM) is a panel data regression model is most appropriate. Based on simultaneous test, Gross Domestic Product (GDP), inflation, the minimum of wage, and the number of population simultaneously have an impact on the unemployment rate. Based on the effect validity test, Gross Domestic Product (GDP) significant negative effect on the unemployment rate, the minimum wage and population has a significant positive effect on the unemployment rate, while inflation does not have a significant effect on the unemployment rate in Surakarta Residency from 1999-2013.